Rekonstruksi Tanggung Jawab Negara dalam Perlindungan Hak Asasi Manusia dalam Perspektif Hukum Tata Negara Modern - Adhelia Puteri Maharani; Eko Handoyo (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the state’s responsibility in protecting human rights based on Article 28I paragraph (4) of the 1945 Constitution of the Republic of Indonesia and Article 71 of Law Number 39 of 1999. The research is motivated by the gap between normative guarantees and their implementation in practice. The objective of this study is to analyze the normative framework of state obligations and assess their effectiveness in ensuring human rights protection. This research employs a normative legal method with statute and conceptual approaches, using primary and secondary legal materials analyzed qualitatively. The findings indicate that although Indonesia has a strong constitutional and legal foundation, the implementation of state responsibility remains suboptimal, particularly in institutional effectiveness, law enforcement, and victim protection. The study highlights the need for strengthening institutional coordination, improving accountability, and ensuring comprehensive remedies for victims. The implications suggest that human rights protection must be realized not only at the normative level but also through consistent and effective implementation in practice.